Acute Effects of the Novel Psychoactive Drug 2C-B on Emotions. (12th October 2015) - González, Débora; Torrens, Marta; Farré, Magí
Abstract : Background . 2C-B (Nexus) is one of the most widespread novel psychoactive substances. There is limited information about its pharmacological properties, and few studies in humans concern its acute and chronic effects. 2C-B has been classified as a stimulant, hallucinogen, entactogen, and/or empathogen. Objectives . To evaluate the emotional, subjective, and cardiovascular effects of 2C-B. Methods . Twenty healthy recreational 2C-B users (12 women) self-administered a 20 mg dose of 2C-B. Evaluations included emotional (IAPS, FERT, and speech), subjective (visual analog scales, ARCI, VESSPA, HRS, and POMS questionnaires), and cardiovascular effects (blood pressure and heart rate). Results . Positive subjective effects predominated with a reduction of anger under the influence of 2C-B. It did, however, increase reactivity to negative emotional stimuli and decrease the ability to recognize expressions of happiness. Augmented emotionality in speech could be appreciated by others. 2C-B induced euphoria and well-being, changes in perceptions, and slight hallucinogenic states. Mild sympathetic actions were observed. Conclusions . The specific profile that 2C-B exerts on emotions suggests its classification as an entactogen with psychedelic properties.